Comparison of Two Models of Community Based Trauma Healing Programs for Children - Ajduković, Marina; Ajduković, Dean (1999)
The goal of the first project was to promote and potentially institutionalize the understanding and practices of trauma healing, conflict resolution, bias awareness and reduction, and peace-living through the schools training medium. The beneficiaries were 103 elementary school children and 8 teachers in two local communities. The goal of the second project was to facilitate psychological and social transition of refugee children and their families, and to help raise professional competence of resettlement communitie's care-providers to take active part in the reconstruction process with regard to children's psychosocial needs. Direct beneficiaries were 70 children and 27 local professionals, indirect beneficiaries were 350 children and 27 teachers. The assumption of both projects was that professional skills and competence extend beyond specific war-related needs and play important role in fostering social reconstruction in a community traumatized by war. Although both project were specific responses to the needs of children, some lessons learned have importance for communities faced with violence and dramatic social changes. These include (1) trauma healing and non-violent problem solving training program for all children in a certain traumatized community, (2) social skills and support groups for children with problems in social adjustment, (3) treatment for children suffering from posttraumatic stress reactions. While the last two interventions are need-driven and are offered only when needed, the first one should become a regular part of school curriculum. (4) Interventions should be appropriate for a group format, should help restore children's faith in themselves and community, foster community building, help integrate painful collective experiences, simple enough to teach para-professionals in order to create a ripple effect, should be culturally appropriate, children caretakers should also be a target group.
Projekt MZOS
ENG